The biogeochemistry of lipid derived infochemical signals in the ocean - Edwards, Bethanie Rachele (Massachusetts Institute of Technology, 2016)
Thesis: Ph. D., Joint Program in Oceanography/Applied Ocean Science and Engineering (Massachusetts Institute of Technology, Department of Earth, Atmospheric, and Planetary Sciences; and the Woods Hole Oceanographic Institution), 2016. Cataloged from PDF version of thesis. Includes bibliographical references. The role of oxylipins in ocean biogeochemistry was investigated using microcosm amendment experiments, environmental lipidomics, and culture based studies. Oxylipins are a bioactive class of secondary metabolites produced by diatoms and other eukaryotic phytoplankton. Previous research has focused mainly on one class of oxylipins, polyunsaturated aldehydes (PUAs), and their impacts on copepods. And few studies have looked at the impacts of oxylipins in situ. Here I show that oxylipins have the potential to impact carbon flux attenuation, oxylipin production in situ is linked to diatom bloom decline and viruses, and oxylipins deter microzooplankton grazing. Sinking particles collected in the North Atlantic were determined to be hot spots for PUAs with concentrations in the micromolar range. Natural particle associated microbial communities exhibited a dose dependent response to PUAs. Stimulatory PUA concentrations ranged from 1-10 ptM, resulting in enhanced remineralization of organic matter by particle associated microbes. Thus, PUAs produced during bloom decline may lead to greater flux attenuation and nutrient recycling. A novel lipidomics approach was applied along a cruise track in the California Coastal System revealing that canonical diatom free fatty acids and oxylipins dominated the dissolved lipidome and oxylipin abundance was correlated with diatom bloom demise as assessed by phaeophytin and biogenic Si. RNA viruses were likely the cause of diatom bloom demise and may have induced oxylipin production. The link between viruses and oxylipins represents a new infochemical signaling pathway in the ocean. Many oxylipins that are novel to the marine environment were also identified. The dissolved ...